Marketing Stimulus and its Impact on Green Product Purchase Intention of Customer: with the Mediating Role of Customer Attitude - M. S. Ishar Ali; M. Siraji (International Journal on Economics, Finance and Sustainable Development, 2021)
The main aim of this study is to investigate the impact of marketing stimulus on customer intention to purchase green products and customer attitude, as well as to examine the mediating role of customer attitude between marketing stimulus and green product purchase intention. A survey was used to gather information from the residence of ampara district, total of 350 questionnaires were issued and 310 responses were received . The proposed model was tested using structural equation modeling, and confirmatory factor analysis was used to assess the reliability and validity. The main finding of this study is that the marketing stimulus influences consumer intention to buy green products and customer attitude positively, while customer attitude fully mediate the relationship between marketing stimulus and green product purchase intention among respondents.